The Qualities of Leadership: Direction, Communication, and Obfuscation. - Dewan, T; Myatt, D (2008)
What is leadership? What is good leadership? What is successful leadership? Answers emerge from our study of a formal model in which followers face a coordination problem: they wish to choose the best action while conforming as closely as possible to the actions of others. Although they would like to do the right thing and do it together, followers are unsure about the relative merits of their options. They learn about their environment and the likely moves of others by listening to leaders. These leaders bridge differences of opinion and become coordinating focal points. A leader's influence increases with her judgement (her sense of direction) and her ability to convey ideas (her clarity of communication). A leader with perfect clarity enjoys greater influence than one with a perfect sense of direction. When followers choose how much attention to pay to leaders, they listen only to the most coherent communicators. However, power-hungry leaders who need an audience sometimes obfuscate their messages, but less so when their followers place more emphasis on conformity than on doing the right thing.